The GRAPPA-OMERACT Psoriatic Arthritis Working Group at the 2018 annual meeting: report and plan for completing the core outcome measurement set - Leung, Y; Orbai, A; Ogdie, A; Coates, L; De Wit, M; Callis Duffin, K; Eder, L; Gladman, D; Goel, N; Mease, P; Strand, V; Fitzgerald, O; et al. (Journal of Rheumatology, 2019)
The Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA)-Outcome Measures in Rheumatology (OMERACT) Psoriatic Arthritis (PsA) Working Group reported at the 2018 GRAPPA annual meeting on the outcome of the OMERACT 2018 Conference in Terrigal, Australia. The working group presented the endorsement of the 66/68 joint count for the assessment of peripheral arthritis and the provisional endorsement of the PsA Impact of Disease 12 questionnaire for the assessment of PsA-specific health-related quality of life in PsA randomized controlled trials and observational studies. In this report, the group presents its plan to seek OMERACT endorsement for outcome measures that address the domains of MSK disease activity for enthesitis and dactylitis, physical function, fatigue, and structural damage following the OMERACT Filter 2.1 methodology.